War in Ukraine in Political Language in the Spanish Media: A Discourse Analysis of Written Press - Mockova, Nina; Spišiaková, Mária (Íkala, Revista de Lenguaje y Cultura, 2025)
War in Ukraine has had global reverberations. The most discussed topics both in the press and in the media are weapons supply, hosting refugees and Spain’s direct involvement in the conflict. The present research article reports a qualitative study conducted from a corpus collected since the outbreak of war in Ukraine in February 2022, until Spain’s general elections in July 2023, and analyzes 80 communiqués. The study is based on the discourse analysis by representatives of the most important political parties currently active in Spain, and by the media. This article analyzes the attitudes of politicians in the Spanish political scene, their rhetorical strategies and other language resources deployed in the media, and the political language used by politicians. The results show the existence of tendencies towards populism in both far right-wing and left-wing parties while, at the linguistic level, metaphors, phraseology units, euphemisms, stylistic neologisms, and the reuse of obsolete words abound. This research will complement political language studies in central Europe, and will help to compare political language studies in other countries.